A expressão variável do futuro do pretérito no português falado em Feira de Santana e Salvador - Bahia - Santos, Aline da Silva (2024)
In this study, we analyze the variable expression of the conditional future tense in the Portuguese spoken in Feira de Santana and Salvador-BA. The future tense has temporal and modal characteristics, expresses different semantic notions, such as the value of hypothesis, uncertainty, possibility, and alternates its use, especially in the informal variety, with the imperfect past tense. Thus, there are variations between the future tense (FP) and the imperfect tense (IP), in contexts such as, for example, "if I could, I would study more" or "if I could, I would study more" and even with the periphrastic forms I would study and I would study, respectively; in addition to also occurring in modal auxiliary verbs, for example: should study/should study. Arguing that the alternation between FP and IP happens in a supra-regional and following the foundations of the Theory of Linguistic Variation and Change (Weinreich; Labov; Herzog, 2006 [1968]), data from 70 DID (Dialogue between Informant and Documenter) interviews of urban speech in Feira de Santana and Salvador were analyzed in this research. The 36 interviews from Feira de Santana are part of the database of the project The Portuguese Language in the Semi-arid Region of Bahia, coordinated by professors Norma Lucia F. de Almeida and Zenaide de O. Novais Carneiro; the Salvador samples are composed of 24 interviews from the Salvador Spoken Portuguese Studies Program (PEPP), coordinated by Professor Norma Lopes, and 10 that belong to the Cultured Urban Norm in Brazil (NURC) project, coordinated by Professor Jacyra Andrade Mota. In order to verify the linguistic and social contexts that motivate this variation, the occurrences of the linguistic phenomenon were submitted to the GoldVarb X program, which revealed that PI, the variant used as an application rule, is more frequent (56%). In the main analysis of the data, the program also selected the following groups of linguistic factors as significant: 'type of text', 'temporal value vs. modal value', 'syntactic-semantic environment', 'phonic salience' and 'temporal reference'. Respectively, the factors in each group that favor the use of IP in PF contexts are narrative sequence (0.70), temporal value (0.79), hypothetical period in canonical order: protasis + apodase (0.69) and embedded clause with coooccurring protasis (0.90), verbs of 2nd and 3rd conjugations (0.67), temporal reference in the past tense (0.65). Regarding the social factors, the 'informant's education' was selected, with the IP favored by the informants of elementary school (0.65) and high school (0.64), and the 'informant's age group', whose factor favoring the IP is age group III (0.68), with informants from 65 years old. Although PI has been favored in these contexts, PF stands out in other factors that make up each variable, therefore, it was found that the alternation between the variants is balanced and points to a stable variation.